GREEN CHEMISTRY MEETS ONCOLOGY: EXPLORING GLORIOSA SUPERBA AS A NATURAL ANTICANCER AGENT - S. MEGALA, NIRMAL KUMAR GOPALA KRISHNAN, DHESA PRIYA GOPALA KRISHNAN, S. R. PARANTHAMAN, P. SARANRAJ, S. MOHAN KUMAR, IADALIN RYNTATHIANG, MUKESH KUMAR DHARMALINGAM JOTHINATHAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The well-known medicinal herb Gloriosa superba, which is highly valued in traditional Indian medicine, is quickly becoming a powerful source of innovative treatments. With an emphasis on the antibacterial and anticancer potential of G. superba tubers and seeds, this study examines their extensive phytochemical profile and remarkable biological qualities. Advanced techniques like Thin Layer Chromatography (TLC), Column Chromatography, Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectrometry (GC-MS) were used to identify a wide range of bioactive compounds, including fatty acids, phenolics, gloriosine, colchicine and flavonoids. The tuber extract showed a maximal inhibition zone of 20 mm, indicating that the extracts exhibited high antibacterial activity against multidrug-resistant Staphylococcus aureus (MRSA). Simultaneously, Methanolic seed extracts shown exceptional lethal effects on breast cancer cells MDA MB231. Yielding an IC₅₀ value of 19.52 µg/mL in MTT assays. These findings highlight G. superba as a natural, eco-friendly alternative to synthetic drugs, offering promising avenues for future antimicrobial and anticancer drug development.